Failure of early B cell tolerance and possible BCR signaling dysregulation underlie NF155-mediated autoimmune nodopathies - Bhaskar Roy; Abeer H. Obaid; Zhenjian Wang; Kristof G. Kovacs; Sarah Ohashi; F. Naz Cemre Kalayci; Daniel Joo; Gianvito Masi; Carmina Coppola; Sameeran Das; Amanda L. Hernandez; Lorena Martin-Aguilar; et al. (Proceedings of the National Academy of Sciences, 2026)
Autoimmune nodopathies (AINs) are rare acquired autoimmune neuropathies with distinct clinical features and circulating autoantibodies, often of the immunoglobulin G4 (IgG4) subclass, targeting proteins at the node of Ranvier. Defects in B cell tolerance checkpoints have been implicated in several autoimmune diseases, including MuSK-positive myasthenia gravis, another IgG4 autoantibody-mediated disease. Here, we investigated whether tolerance defects exist in neurofascin-155-mediated AIN (NF155-AIN), using a well-established assay, by generating recombinant antibodies from new emigrant (NE) and mature naive (MN) B cells from three NF155-AIN patients, and tested them for polyreactivity and autoreactivity. Additionally, we analyzed the transcriptome of peripheral blood mononuclear cells, with a particular focus on naive B cells and CD4+ T cells at the single-cell level, and characterized cell–cell interactions. NF155-AIN patients have an elevated frequency of polyreactive B cells in the NE (37.4% compared to 9.7% in healthy controls (HCs), P = 0.03) and MN (31.5% compared to 10.5% in HCs, P = 0.03) compartments, consistent with a breach in early B cell tolerance checkpoints. In this unbiased exploratory transcriptomics analysis, we observed potentially abnormal B cell receptor (BCR) signaling characterized by low CD79B, CSK, BLNK, and BTK expression, and possible impaired CD4+ T cell regulatory function. Moreover, comparison with chronic inflammatory demyelinating polyneuropathy, a related autoimmune neuropathy, suggested that these differences are specific to NF155-AIN. A breach in early B cell tolerance checkpoints, with defective BCR signaling, and disrupted T cell–B cell interactions in NF155-AIN, may contribute to the development of pathogenic autoreactivity.